2010
DOI: 10.1007/s12012-010-9083-x
|View full text |Cite
|
Sign up to set email alerts
|

Glycolaldehyde Induces Oxidative Stress in the Heart: A Clue to Diabetic Cardiomyopathy?

Abstract: Cardiovascular complications account for 80% of the mortality related to diabetes mellitus. Hyperglycemia is believed to be the major culprit of angiopathy and cardiomyopathy. High glucose levels and oxidative stress cause elevation of Advanced Glycation End-products that are known to contribute to diabetic complications and correlate with many diseases. However, there are few reports describing the effects of glycating agents other than glucose. Here, we aimed to evaluate the effects of glycolaldehyde (GA) on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 44 publications
1
16
0
Order By: Relevance
“…An increase in the production of ROS by AGEs conforms to the pathogenesis of diabetic cardiomyopathy [9,52,53]. Our results demonstrate that AGEs enhance the production of ROS and increase LDH.…”
Section: Discussionsupporting
confidence: 78%
“…An increase in the production of ROS by AGEs conforms to the pathogenesis of diabetic cardiomyopathy [9,52,53]. Our results demonstrate that AGEs enhance the production of ROS and increase LDH.…”
Section: Discussionsupporting
confidence: 78%
“…Both "nadph" and "nadp" are valuable metabolites in l-xylulose (l-xylulose is obtained by "nadph" and "nad" reduction with "d-xylulose" [36]) which is intensively used in diabetes diagnosis. While reaction 1951 is glycolaldehyde dehydrogenase, glycolaldehyde has been shown to play a significant role in diabetic cardiomyopathy [37]. And "pi" is a critical component in the disturbance of diabetes [38].…”
Section: Resultsmentioning
confidence: 99%
“…The name of Reaction 1951 is Glycolaldehyde dehydrogenase. It has been shown that glycolaldehyde has a significant role in the development of diabetic cardiomyopathy [30]. And "pi" in reaction 2700 is a key component in the disturbance of Diabetes [31].…”
Section: Resultsmentioning
confidence: 99%